An analytical study of some biodynamic variables of the Egyptian world champion weightlifter (Mahmoud Hosny) in the snatch lift - Al-Atabi, Asst.Prof.Dr.Saif Ali Nasser (Sulaimani Journal for Humanities, 2026)
The research aims to analyze the biodynamic variables of the Egyptian world champion weightlifter (Mahmoud Hosny), who won three gold medals in the weight category (89) kg, in the World Youth Championship held in Mexico. A video clip of the two sides of the snatch lift was obtained, and the clip was cut and placed inside the icon of the motion analysis program (Kenova). Through working on the icon of the program, the variables were analyzed, through which the researcher concluded that the weightlifter's performance is characterized by high skill and is based on the foundations of applied sciences in terms of employing angles in a way that serves the motor duty. The most important recommendation of the researcher is to emphasize to coaches the necessity of resorting to these results and benefiting from employing mechanical concepts to serve the sport of weightlifting.